Seed Size, Fecundity and Postfire Regeneration Strategy Are Interdependent in Hakea - El-ahmir, S.; Lim, S.L.; Lamont, Byron; He, Tianhua (Public Library of Science, 2015)
Seed size is a key functional trait that affects plant fitness at the seedling stage and may vary greatly with species fruit size, growth form and fecundity. Using structural equation modelling (SEM) and correlated trait evolution analysis, we investigated the interaction network between seed size and fecundity, postfire regeneration strategy, fruit size, plant height and serotiny (on-plant seed storage) among 82 species of the woody shrub genus, Hakea, with a wide spectrum of seed sizes (2–500 mg). Seed size is negatively correlated with fecundity, while fire-killed species (nonsprouters) produce more seeds than resprouters though they are of similar size. Seed size is unrelated to plant height and level of serotiny while it scales allometrically with fruit size. A strong phylogenetic signal in seed size revealed phylogenetic constraints on seed size variation in Hakea. Our analyses suggest a causal relationship between seed size, fecundity and postfire regeneration strategy in Hakea. These results demonstrate that fruit size, fecundity and evolutionary history have had most control over seed size variation among Hakea species.